What is new in type 1 diabetes? - Lernmark, Åke (Henry Stewart Talks, 2013)
Type 1 diabetes is an autoimmune disease, Specific eradication of pancreatic beta cells, Environmental factors that trigger the appearance of islet autoantibodies, The pathogenesis involve factors that either accelerate or decelerate progression to clinical onset of diabetes, A combination of genetic typing for HLA genes and determination of islet autoantibodies make type 1 diabetes a predictable disease
Archived at 2023/02/28